Binocular imbalance in patients after implantable collamer lens V4c implantation or femtosecond laser-assisted in situ keratomileusis for myopia with presbyopia - Ye, Yuhao; Zhang, Zhe; Niu, Lingling; Shi, Wanru; Wang, Xiaoying; Yan, Li; Zhou, Xingtao; Zhao, Jing (Frontiers in Neuroscience, 2023)
Aim: To investigate the long-term safety, efficacy, and binocular balance of monovision surgery using Implantable Collamer Lens (ICL) V4c implantation and Femtosecond Laser-Assisted in Situ Keratomileusis (FS-LASIK) for the treatment of myopic patients with presbyopia. Methods： This case series study involved 90 eyes of 45 patients (male/female=19/26; average age:46.27±5.54 years; average follow-up time:48.73±14.65 months) who underwent the aforementioned surgery to treat myopic presbyopes. Data on manifest refraction, corrected distance visual acuity, dominant eye, presbyopic addition, intraocular pressure, and anterior segment biometric parameters were collected. The visual outcomes and binocular balance at 0.4 m, 0.8 m, and 5 m were documented. Results: The safety index for the ICL V4c and FS-LASIK groups were 1.24±0.27 and 1.04±0.20 (p=0.125), respectively. Binocular visual acuity (logmar) for 0.4 m, 0.8 m, and 5m were -0.03±0.05, -0.03±0.02, and 0.10±0.03 for the ICL V4c group, and -0.02±0.09, -0.01±0.02, and 0.06±0.04 for the FS-LASIK group, respectively. The proportions of all patients with imbalanced vision at 0.4m, 0.8m, and 5m distances were 68.89%, 71.11%, and 82.22%, respectively. (all p>0.05 between the two groups). There were significant differences in refraction between the balanced and imbalanced vision for patients at 0.4 m distance (for non-dominant eye spherical equivalent [SE]: -1.14±0.17D and -1.47±0.13D, P<0.001), 0.8 m distance (for preoperative ADD:0.90±0.17D and 1.05±0.11D, P=0.041), and 5 m distance (for non-dominant SE: -1.13±0.33D and -1.42±0.11D, P<0.001). Conclusion: ICL V4c implantation and FS-LASIK monovision treatment demonstrated good long-term safety and binocular visual acuity at various distances. After the procedure, the imbalanced patients' vision is primarily related to the age-related presbyopia and anisometropia progression caused by the monovision design.